HAK WARIS KHUNTSA MUSYKIL DAN METODE PENYELESAIANNYA - Amri, Amsanul; Ajirna, Cut (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2025)
Islamic inheritance law is regulated according to qath'i wurudz and dalalah. This legal certainty of inheritance covers who has the right to be an heir, who is covered by the hijab, up to the amount of shares received. Even so, the inheritance law of abstruse khuntsa is a complicated issue in determining gender, which in turn of course also influences the portion of the inheritance that is received later. The purpose of this research is to determine the inheritance law of abstruse khuntsa and the method for solving it. This research uses a descriptive analysis method with a qualitative research type with normative juridical research characteristics, considering that this research is legal research. The results of the research identified that abstruse khuntsa are people who have multiple genitals or none at all. As for the method of resolution, there are differences of opinion among scholars. Some scholars give inheritance rights to the smallest of two choices when they are considered male and female. The opinion of other scholars gives half of the accumulation he is considered to be men and women